Excretion of FDG into saliva and its significance for PET imaging - Stahl, A.; Dzewas, B.; Schwaiger, M.; Weber, W. A. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: Assessment of the salivary excretion of FDG and its significance during PET imaging. Methods: Salivary samples from 16 patients were obtained during the first three hours after FDG injection and their activity concentrations were measured. Furthermore, regional FDG accumulations in whole body PET scans (60 min p. i., ROI technique) were determined in the following locations: vestibulum oris, floor of the mouth, hypopharynx, parotid gland, submandibular gland. This ROI analysis was repeated after drinking water (0.2 l) and a second scan (120 min p. i.). Results: The salivary FDG concentrations (SUV) at the first, second and third hour p. i. were 0.2 ± 0.1, 0.4 ± 0.2, and 0.3 ± 0.2, respectively. The FDG uptake in the investigated cranial and cervical sites ranged from SUV 1.2 ± 0.5 in the major salivary glands to 2.1 ± 0.5 in the floor of the mouth. These values remained unchanged after drinking of water. Conclusion: The salivary FDG concentration is higher than expected from the low physiologic content of glucose. This may – similarly to renal excretion – reflect a different behavior of FDG and glucose during reabsorption processes. Nevertheless, the salivary concentration of FDG is so low that no relevant influence on PET imaging is to be expected. Accordingly, the drinking of water prior to the scan is of no benefit for FDG PET imaging of the head and the neck.
Keywords: Fluorine-18-fluorodeoxyglucose; positron emission tomography; saliva